An Analysis of Rural Poverty Alleviation Programs and Challenge in Assam (A Micro Level Study of Margherita Block of Tinsukia District) - Deori, Bhupen Deori (International Research Journal of Management, IT & Social Sciences, 2015)
The research was intended to describe the development of the rural people, the country cannot claim to be a developed country. Not only India, every developing country of the world has been trying to reduction of poverty because of the poverty eradication is considered an integral to humanityâs mission for their sustainable development. It is a concept of global dialog and vital for the attainment of international goals. The government of India as well as states government has launches some poverty eradication program for the development of rural peoples, but all these poverty alleviation program are did not yield the desired result due to various shortcomings. Successful implementation of these program required appropriate policy framework, adequate funds and effective delivery mechanism. An effective and responsive district level field machinery with a high degree of commitment, motivation, professional competence and above all integrity has been recognized as one of the pre-requisites for successful implementation of an anti-poverty strategy.